PERUBAHAN WARNA PADA BERCAK DARAH BERDASARKAN PERBEDAAN WAKTU SIMPAN DAN LUAS BERCAK DARAH YANG TERBENTUK PADA KAIN DENIM, KATUN, DAN POLYESTER - Ni Kadek Aryani Sumbawati; I Ketut Junitha; Ni.G.A. Manik Ermayanti (Program Studi Biologi Universitas Udayana, 2024)
Blood is a thick liquid that is in the blood vessels of the body, which is red because it contains hemoglobin to circulate oxygen and nutrients throughout the body. If blood comes out of the body due to sharp or blunt blows, either intentionally or unintentionally, it will end up on your clothes. Clothing is made from fabric composed of fibers, generally in the form of denim, cotton and polyester. This research was conducted to determine the color changes that occur in blood spots based on storage times of 0 days, 15 days and 30 days and to determine the area of ​​blood spots that form on denim, cotton and polyester fabrics. The method used in this research is measuring the diameter and observing the color changes that occur. The research design used in this research was (RAL) a completely randomized design with repetition 3 times. The results of the research showed that there were color changes that occurred from fresh red, dark brown, and light brown. Meanwhile, the area of ​​fabric obtained from denim fabric has the smallest area compared to cotton and polyester fabrics. However, the polyester fabric has black stains around it.